2013
DOI: 10.18097/pbmc20135904443
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants in erythrocytes in aging and dementia

Abstract: Age of patients and brain oxidative stress may contribute to pathogenesis of Alzheimer's disease (AD). Erythrocytes (red blood cells, RBC) are considered as passive “reporter cells” for the oxidative status of the whole organism and are not well studied in AD. The aim of this work was to assess whether the antioxidant status of RBC changes in aging and AD. Blood was taken from AD and non-Alzheimer's dementia patients, aged-matched and younger controls. In vivo antioxidant status was assessed in each of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In this study, plasma and erythrocyte levels of PLOOH were significantly decreased in both low-and high-dose groups compared to the control group. This finding maybe significant because it has been suggested that elevated erythrocyte membrane oxidation is associated with neurodegenerative diseases (Bosman et al 1991;Giavarotti et al 2013;Goodall et al 1994;Kawamoto et al 2005;Kawamoto et al 2013;Kosenko et al 2013).…”
Section: Clinical Trialsmentioning
confidence: 84%
“…In this study, plasma and erythrocyte levels of PLOOH were significantly decreased in both low-and high-dose groups compared to the control group. This finding maybe significant because it has been suggested that elevated erythrocyte membrane oxidation is associated with neurodegenerative diseases (Bosman et al 1991;Giavarotti et al 2013;Goodall et al 1994;Kawamoto et al 2005;Kawamoto et al 2013;Kosenko et al 2013).…”
Section: Clinical Trialsmentioning
confidence: 84%